Ultra low power current mirror design with enhanced bandwidth. (July 2021) - Pritty,; Jhamb, Mansi
Abstract: Current mirrors are fundamental to every analog block. This work proposes a novel design of low voltage, low power, and improved performance current mirror. The proposed current mirror circuit has negative and positive feedback paths to obtain maximal output resistance at 12 ​μA input current. Its performance is validated @ 90 ​nm technology at 0.75 ​V supply voltage. The bandwidth of the proposed Current mirror design is 748.847 ​MHz, and the minimum supply voltage is 0.045 ​V. Moreover, a remarkably high output resistance of 250 ​GΩ accomplished, it is the maximum value attained as compared to CMOS based state-of-art designs. The proposed design consumes 19.436 ​μW power, and the current transfer value is 0.016.